Solution conformation of gramicidin S: An intramolecular nuclear Overhauser effect study - Huang, Dee-Hua (1981)
The solution conformation of gramicidin S in deuterated dimethyl sulfoxide was investigated by using the intramolecular nuclear Overhauser effect experiment. Experimental Overhauser enhancements were compared with predicted values for each of the nine most-stable conformations (M1-M9) calculated by Dygert et al. on the basis of energy-minimization procedures [Dygert, M., Gō, N. & Scheraga, H. A. (1975) Macromolecules 8, 750-761]. By using statistical hypothesis testing, the three lowest-energy conformations (M1, M2, and M3) were shown to give the best fit with the experimental data. All other conformations (M4-M9) were found to be inconsistent with the experimental data.